Implementing of Restorative Justice to Build the Criminal Justice System in Indonesia: A Study of the Batak Toba Justice System - Rochaeti, Nur; Prasetyo, Mujiono Hafidh; Park, Ji Hyun (LAW REFORM, 2023)
The pursuit of fairness and harmony between the realization of rights and duties is a cornerstone of human progress. Restorative justice case resolution represents an endeavor to introduce a non-punitive procedure into Indonesia's criminal justice system as part of its ongoing effort to modernize its legal framework. Restorative justice focuses on healing criminal behavior's harm and shattered relationships. This study examined the feasibility of implementing restorative justice aspects into a national criminal justice system, gaining inspiration from the Toba Batak Indigenous People. The methodology was socio-legal. Dalihan Natolu is recognized as an alternative conflict settlement method for Toba Batak. The traditional leader mediates in this conflict resolution. By Batak customary law, the imposition of sanctions is decided by customary judges or kings. Dalihan Natolu then tells the culprit not to repeat his behavior. Dalihan Natolu involves offenders, victims, families of offenders and victims, and other parties in seeking a fair settlement that emphasizes repair above retribution. This helps Dalihan Natolu solve criminal concerns. In indigenous cultures, customary institutions convene the parties engaged in a crime to provide counsel and find solutions that do not harm or profit only one side. Justice is served, and the victim is not harmed.